Prolonged jaundice, azotomia and leucopenia in a patient with acute type B virus hepatitis - Abdurrahman KADAYIFÇI; Serap ARSLAN; Mustafa BENEKLİ; Mehmet ARSLAN; Cemil SAVAŞ (Turkish Journal of Gastroenterology, 2019)
-